THE USE OF NUMBERED HEADS TOGETHER (NHT) TECHNIQUE IN TEACHING READING RECOUNT TEXT - Mia Siti Kamilah (Journal of English Education Program (JEEP), 2017)
This study investigated the use of Numbered Heads Together (NHT) technique in teaching reading recount text at the eighth grade of a junior high school. Numbered Heads Together (NHT) technique is one of techniques which is derived from cooperative learning method that includes four simple steps: dividing and numbering off students into a group, giving a problem, putting heads together, and calling up the numbered-heads (Slavin, 2005). This study was conducted in qualitative approach, particularly case study. The data were obtained from several sources including classroom observation in four sessions and interview to an English teacher and six students at the eighth grade of a junior high school in Ciamis. The result showed that based on the classroom observation and interview, the use of Numbered Heads Together (NHT) technique was useful and appropriate to attract students’ attention in learning reading, in this case the students could more increase their reading ability. As result of findings of this study, Numbered Heads Together (NHT) is recommended to be used in teaching and learning process to increase students’ reading ability.